2018
DOI: 10.5114/pjr.2018.73291
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound for evaluation of deep venous blood flow in fractured lower extremities

Abstract: PurposeEarly identification of deep venous thrombosis (DVT) in trauma patients would result in an early initiation of treatment, thereby decreasing the frequency of complications. The aim of the current study was to evaluate the role of duplex ultrasound (DUS) in the evaluation of deep venous blood flow in fractured lower extremities to rule out DVT prior to orthopedic surgery.Material and methodsIn this prospective study a total of 58 patients (42 males and 16 females; mean age of 51.5 ± 19.5 years) with frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…The occurrence of DVT was significantly correlated with the fracture site. Similar to the results of Adam et al and Zhang et al [ 16 , 17 ], the incidence of hip fracture (74.90%) was relatively high. Considering that most patients with hip fractures may have three risk factors of Virchow at the same time [ 18 ], we should pay attention to the screening of DVT in these patients with fractures at specific sites and formulate reasonable individualized prevention and treatment strategies.…”
Section: Discussionsupporting
confidence: 88%
“…The occurrence of DVT was significantly correlated with the fracture site. Similar to the results of Adam et al and Zhang et al [ 16 , 17 ], the incidence of hip fracture (74.90%) was relatively high. Considering that most patients with hip fractures may have three risk factors of Virchow at the same time [ 18 ], we should pay attention to the screening of DVT in these patients with fractures at specific sites and formulate reasonable individualized prevention and treatment strategies.…”
Section: Discussionsupporting
confidence: 88%
“…In general, patients who undergo a hip fracture exhibit all three risk factors associated with Virchow’s triad, which contribute to the high occurrence of DVT 40. Besides, we observed statistical differences in the incidence of DVT of different fracture sites ( P <0.01), indicating a similar result as Awadalla Adam’ research, which found that the incidence of DVT after orthopaedic trauma appears to be associated with the sites of fractures 41. Of the multiple fracture sites, we found hip fracture presented with the highest rate of DVT, demonstrating that hip fracture may be a risk factor for DVT.…”
Section: Discussionsupporting
confidence: 83%
“…Among fracture patients, the current routine anticoagulant regimens are used for the prevention and treatment of DVT in patients with different risks, which does not change the current situation that the incidence of DVT is still relatively high.It is particularly important to further clarify independent risk factors for DVT to identify high risk groups.The occurrence of DVT was signi cantly correlated with the fracture site. Similar to the results of Adam and Zhang [12,13] , the incidence of hip fracture (74.90%) was relatively high. Considering that the three risk factors of Virchow were mostly present in the patients with hip fracture [14] .We should pay attention to the screening of DVT in these patients with fractures at speci c sites, and formulate reasonable individualized prevention and treatment strategies.Meizoso et al used RAP score in a retrospective cohort study of 1233 trauma patients and found that transfusion of more than 4 units was an independent risk factor for DVT [15] .The preoperative, intraoperative and postoperative blood transfusion rates of 569 patients in this study were 8.44% (48/569), 29.70% (169/569), and 13.88% (79/569), respectively.It was further found that intraoperative blood transfusion and postoperative blood transfusion were independent risk factors for postoperative DVT, while preoperative blood transfusion was not correlated with DVT.Perhaps we should reconsider the indications and necessity of blood transfusion in practice.Song et al reported that most patients with postoperative DVT had complicated DVT before surgery [16] ,In this study, preoperative DVT occurred in 26.71% of the patients, which was considered to be related to the longer average preoperative waiting time.Most of the current recommendations are that surgery should be performed as soon as possible within 48 hours after trauma to reduce the incidence of VTE [17] .But in practice, 66 percent of patients with hip fractures delayed surgery [18] .The reasons for delayed surgery may be as follows.…”
Section: Discussionsupporting
confidence: 85%